2017
DOI: 10.1002/ar.23578
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Distribution of Myosin Heavy Chain Isoforms Within Single Muscle Fibers

Abstract: Despite many studies looking at the distribution of myosin heavy chain (MHC) isoforms across a transverse section of muscle, knowledge of MHC distribution along the longitudinal axis of a single skeletal muscle fiber has been relatively overlooked. Immunocytochemistry was performed on serial sections of rat extensor digitorum longus (EDL) muscle to identify MHC types I, IIA, IIX, IIY, and IIB. Sixteen fascicles which contained a total of 362 fibers were randomly and systematically sampled from the three EDL mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…4) (Zhang et al, 2010). Other more recent studies have reported similar patterns in normal mammalian muscles (Korfage et al, 2015;Zhang and Gould, 2017).…”
Section: Fiber-type Asymmetriessupporting
confidence: 55%
See 2 more Smart Citations
“…4) (Zhang et al, 2010). Other more recent studies have reported similar patterns in normal mammalian muscles (Korfage et al, 2015;Zhang and Gould, 2017).…”
Section: Fiber-type Asymmetriessupporting
confidence: 55%
“…One of the most dramatic patterns of MHC and other myofibrillar isoform distribution is regional differences in protein content along the length of single fibers (Alway, 1993;Andersen, 2003;Bartnik et al, 1999;Brummer et al, 2013;Edman et al, 1988;Korfage et al, 2015;Larson et al, 2019;Lucas and Hoh, 2003;Lucas et al, 2018;Lutz et al, 2001;Maier, 1994;McLoon et al, 2011;Peuker and Pette, 1997;Rosser et al, 1995;Rubinstein and Hoh, 2000;Rubinstein et al, 2004;Sakuma et al, 1995;Snow et al, 2005;Staron and Pette, 1987;Zhang and Gould, 2017;Zhang et al, 2010). Such regional differences are consistent with the fact that frog muscle fibers exhibit major differences in shortening velocity in different segments from a single fiber (Edman et al, 1985).…”
Section: Fiber-type Asymmetriesmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number of studies have now reported that unique MHC isoforms are frequently expressed within different segments of the same muscle fiber. 7,8,13,[41][42][43][44][45][46][47][48] A common interpretation of asymmetric MHC expression is that different myonuclear domains within single fibers may be uncoordinated in their myofibrillar gene expression. 7,8,42,46 Individual muscle fibers can be up to several millimeters long, and typically contain hundreds of myonuclei.…”
Section: (Continued)mentioning
confidence: 99%
“…The primary antibodies used are well characterized within our laboratory (Koishi et al 1995;Lee et al 2004Lee et al , 2018Zhang & Gould, 2017). In addition, there are mouse monoclonal antibodies against Pax7, myogenin F5D or neonatal F59 (Developmental Studies Hybridoma Bank), MyoD 5.8A (BD Biosciences) or embryonic fast MY32 (Sigma); rabbit polyclonal antibodies against Myf5, MyoD M-318 and myogenin M-225 (Santa Cruz); goat polyclonal antibody against Pax3 (Abcam); p38MAPK and phosphorylated p38MAPK (Cell Signalling).…”
Section: Immunohistochemistrymentioning
confidence: 99%